2017
DOI: 10.1186/s10397-017-1015-3
|View full text |Cite
|
Sign up to set email alerts
|

Dominant hand, non-dominant hand, or both? The effect of pre-training in hand-eye coordination upon the learning curve of laparoscopic intra-corporeal knot tying

Abstract: BackgroundTraining of basic laparoscopic psychomotor skills improves both acquisition and retention of more advanced laparoscopic tasks, such as laparoscopic intra-corporeal knot tying (LICK). This randomized controlled trial (RCT) was performed to evaluate the effect of different pre-training programs in hand-eye coordination (HEC) upon the learning curve of LICK.ResultsThe study was performed in a private center in Asunción, Paraguay, by 60 residents/specialists in gynaecology with no experience in laparosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The outcomes of the aforementioned validation protocols showed that the simulator with usual low-fidelity simulators. As training solutions outside the operation room need to be engineered for the initial training period of surgeons [5,60], and as this simulator main aim is the learning of basic laparoscopic skills, we could assume that this simulator might be a mean to complement the existing contents of basic surgical education. This perspective needs, however, to be confirmed by investigating the implementation of this simulator in an early training stage along with the study of the impact of haptic feedback on learning.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The outcomes of the aforementioned validation protocols showed that the simulator with usual low-fidelity simulators. As training solutions outside the operation room need to be engineered for the initial training period of surgeons [5,60], and as this simulator main aim is the learning of basic laparoscopic skills, we could assume that this simulator might be a mean to complement the existing contents of basic surgical education. This perspective needs, however, to be confirmed by investigating the implementation of this simulator in an early training stage along with the study of the impact of haptic feedback on learning.…”
Section: Resultsmentioning
confidence: 99%
“…To better analyze and understand these results, we should consider that this was a bi-manual task, while the first exercise only involved one hand. Surgery skills required the coordination of the two hands [56] and the ability of using both hands is essential in laparoscopic surgery [7,57] and in open surgery [5]. [58], which can also affect the outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations